2014
DOI: 10.1111/imre.12076
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Livelihoods in Johannesburg: Differential Advantages and Unexpected Outcomes among Foreign-Born Migrants, Internal Migrants, and Long-Term South African Residents

Abstract: Foreign‐born migrants – a group rarely compared with both internal migrants and long‐term residents – are often positioned as the most disadvantaged South African urban population. We use data from a 2008 cross‐sectional household survey conducted in Johannesburg to compare a contextually relevant measure of social capital and livelihood advantages between foreign‐born migrants, internal migrants, and long‐term South African residents. Our findings are counterintuitive and emphasize the need to explore the het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 82 publications
5
17
1
Order By: Relevance
“…This finding concurs with the findings by Valentina et al (2010), showing that refugees and asylum-seekers generally have positive expectations about their future well-being. Furthermore, Myroniuk and Vearey (2014), in their research specific to Johannesburg, found that foreign-born migrants' livelihood outcomes compared well to those of South African citizens.…”
Section: The Derived Expected Well-being Variablementioning
confidence: 99%
“…This finding concurs with the findings by Valentina et al (2010), showing that refugees and asylum-seekers generally have positive expectations about their future well-being. Furthermore, Myroniuk and Vearey (2014), in their research specific to Johannesburg, found that foreign-born migrants' livelihood outcomes compared well to those of South African citizens.…”
Section: The Derived Expected Well-being Variablementioning
confidence: 99%
“…Income is one of the key livelihood outcomes in the framework of sustainable livelihood [27]; income level directly reflects the level of community livelihoods, whereas livelihood assets have a significant impact on community income [45,48,52,[61][62][63][64][65]. Social assets in particular are the most crucial factor affecting residents' income increase [65].…”
Section: Effect Of Livelihood Assets On Community Incomementioning
confidence: 99%
“…Social assets in particular are the most crucial factor affecting residents' income increase [65]. Moreover, the lack of livelihood capital, e.g., social assets, information, etc., is the root cause of community residents having a low income and being mired in poverty [42].…”
Section: Effect Of Livelihood Assets On Community Incomementioning
confidence: 99%
See 1 more Smart Citation
“…While there are undoubtedly high levels of vulnerability among displaced populations, there are often equally high levels of vulnerability among host populations and other migrant populations (Landau and Duponchel, 2011;Myroniuk and Vearey, 2014). Analytically distancing international migrants from these sub-national dynamics significantly limits the ability to develop effective, ethical and politically palatable policy responses.…”
Section: Geographic Scope and Scalementioning
confidence: 99%